Diversifikasi Olahan Daging Itik Hibrida Menjadi Bakso Fungsional Dengan Curing Dalam Nanokapsul Jus Kunyit (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractDuck meat is still not widely used as a raw material for making meatballs. Duck meat has an unpleasant odor, tough texture and high fat content which causes it to be disliked by the consumers. Therefore it is necessary to diversify processed products that are acceptable and healthy. Meatballs are processed products made from ground meat plus fillers (flour and spices, then formed into small balls and boiled). In the form of meatballs, it makes it easier for duck meat to be consumed. The high content of unsaturated fatty acids in duck meat causes the formation of a fishy odor (off-flavor). As a result, the meatball is oxidized and produces a rancid aroma and free radicals. The curing treatment of duck meat in turmeric juice nanocapsules as a source of antioxidants is expected to prevent oxidation and produce functional meatballs. The duck meat was cut into 3 cm x 3 cm sizes, then added 2% turmeric juice nanocapsules with a curing time of 5 minutes. The resulting cured duck meat is then processed into meatballs. The meatballs obtained were analyzed for their antioxidant activity and sensory test. The analysis showed that curing duck meat with a concentration of 2% for 5 minutes produced functional meatballs with bright yellow color, had antioxidant levels and was accepted by consumers.